Business Cycles and Alcohol Consumption: Evidence from a Nonlinear Panel ARDL Approach. (November 2021) - Sadik-Zada, Elkhan Richard; Niklas, Britta
Abstract: This study revisits the relationship between economic variables and alcohol consumption from a macro perspective. Focusing explicitly on the asymmetries of the responsiveness of alcohol consumption during the expansion and contraction phases of the business cycle, asymmetric panel estimators are employed. We employ a nonlinear autoregressive distributed lag model for a panel of 24 countries for the period 1961 to 2014. Findings show that expansion leads to a long-term increase in average alcohol consumption, while during contraction, the level of average alcohol consumption persists. Expansion, together with a pronounced reduction in the unemployment rate could, however, lead to a net reduction of gross alcohol and wine consumption. Nonetheless, if the recession corresponds with a surge in unemployment, this leads to a long-run increase in the level of total gross alcohol consumption but a decrease in wine and beer consumption. Reduction in unemployment does not lead to a reduction in beer consumption, as pre-expansion levels of beer consumption persist. (JEL Classifications: E32, I19, L66)